Interaction of Salmonella enterica Serotype Typhimurium with Dendritic Cells Is Defined by Targeting to Compartments Lacking Lysosomal Membrane Glycoproteins - García-Del Portillo, Francisco (American Society for Microbiology, 2000)
Dendritic cells (DCs) play a central role in the generation of acquired immunity to infections by pathogenic microorganisms. Salmonella enterica serotype Typhimurium is known to survive and proliferate intracellularly within macrophages and nonphagocytic cells, but no data exist on how this pathogen interacts with DCs. In this report, we show the capacity of serotype Typhimurium to survive within the established mouse DC line CB1. In contrast to the case for the macrophage model, the compartments of DCs containing serotype Typhimurium are devoid of lysosomal membrane glycoproteins and the PhoPQ two-component regulatory system is not essential for pathogen intracellular survival.